The Reliability of the Progression of Autonomies Scale Applied on Acquired Brain Injured Patients - Arcuri, Francesco; Cortese, Maria Daniela; Riganello, Francesco; Lucca, Lucia Francesca; Serra, Sebastiano; Mazzucchi, Anna; Cerasa, Antonio; Tonin, Paolo (Frontiers in Neurology, 2019)
The Progression of Autonomies Scale is a behavioral scale useful to assess the autonomy levels in acquired brain-injured patients. It provides a broad profile, assessing different domains of human activities ranging from personal, domestic and extradomestic Autonomies. This cross-sectional study is aimed at evaluating the reliability of this scale on a large cohort of ABI patients. Fifty-one brain-injured patients (49% traumatic, 33,33% hemorrhagic, 17,64% other etiologies), hospitalized in the S. Anna Institute of Crotone, Italy (mean age male 46.08 ±14.53 and mean age female patients 43.2±11.3) were recruited. We found a high level of reliability of the scale, with a coefficient at the intrarater agreement between substantial (0,61 ≤ k ≤ 0,8) and almost perfect (0,81 ≤ k ≤ 1), and almost perfect at the test-retest. We confirm that the PAS is a well-structured tool for the assessment of the autonomy levels in brain-injured patients. These findings encourage the application of this scale in the clinical practice of rehabilitation unit to design a tailored rehabilitation treatment on real goals and to monitor the generalization of the recovered abilities to the daily routine activities.